Structural decoupling between the VET and the employment systems: challenges manifested in assessment of practical training - Ümarik, Meril [Verfasser]; Loogma, Krista [Verfasser]; Hinno, Krista [Verfasser] (My University, 2010)
"This article aims to analyse how structural decoupling, which is an especially relevant problem for school-based vocational education and training (VET) systems, reveals itself in the assessment of practical training. Niklas Luhmann's social system theory has been applied to the analysis of assessment practices as a communication act between the VET and the employment systems. This analysis is based on empirical data gathered by semi-structured interviews of different stakeholders in the assessment process from two fields of the VET system - the training of nurses and of information technology/IT specialists. The analysis explores several problems in assessment practices, including fictitious assessment practices, low quality of training and motivation of workplace trainers, and also the lack of correspondence between the school curriculum and the competence base needed in the real workplace. In this study, some of these challenges are explained by communication disruptions in Luhmann's sense and the others by the structural decoupling between the VET and the employment systems." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; L 6.2.3 Evaluation; T 2.6 Systemtheorien; I 2.2.2 Osteuropa; Berufsausbildung; Krankenschwester; IT-Beruf; Praxisbezug; Evaluation; Systemtheorie; Lernortkooperation; Beziehung Bildungssystem Beschäftigungssystem; Estland